2020
DOI: 10.1111/jar.12700
|View full text |Cite
|
Sign up to set email alerts
|

“She’ll be able to live independently… as long as I’m around”: The “lived” experience of parenting a child with 22q11.2 deletion syndrome in the transition to adulthood

Abstract: Background 22q11.2 deletion syndrome (22q11DS) is the most common microdeletion syndrome. Parents of emerging adults with 22q11DS have an intense and ongoing involvement in their child's life. This study explores the lived experience of parents in relation to their child becoming independent and establishing intimate relationships. Method Interpretative phenomenological analysis was used to explore the positive and negative experiences of five parents of emerging adults with 22q11DS. Results Supervised indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To be included in the study SCWs needed to (1) provide direct support for adults with intellectual disabilities (2) work within community living services or day services and (3) speak and read English language. Those who wished to participate were screened for eligibility (Goodwin et al, 2019) before their written consent was secured. Eighteen SCWs were purposively recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
“…To be included in the study SCWs needed to (1) provide direct support for adults with intellectual disabilities (2) work within community living services or day services and (3) speak and read English language. Those who wished to participate were screened for eligibility (Goodwin et al, 2019) before their written consent was secured. Eighteen SCWs were purposively recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneous attitudes were expressed toward the sexual needs and feelings of people with intellectual disabilities within five studies focusing on support staff [38,40,42,48,49], five on relatives [44,[50][51][52][53], and two studies that took the perspectives of both into account [47,54]. On the one hand, several support staff and relatives agreed that people with intellectual disabilities have the same sexual feelings, in the words of a relative "as the rest of us" [51, p. 285; 40, 47].…”
Section: Sexual Needs and Feelings Of People With Intellectual Disabi...mentioning
confidence: 99%
“…On the one hand, several support staff and relatives agreed that people with intellectual disabilities have the same sexual feelings, in the words of a relative "as the rest of us" [51, p. 285; 40, 47]. On the other hand, some support staff and relatives experienced difficulties recognizing the sexual feelings of people with intellectual disabilities [50,53,54]. Moreover, some support staff indicated that the presence of sexual feelings depended on clients' age, gender, and/or the severity of their disability [42,49].…”
Section: Sexual Needs and Feelings Of People With Intellectual Disabi...mentioning
confidence: 99%
See 2 more Smart Citations